2022
DOI: 10.1002/pls2.10077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical modification of crosslinked low‐density polyethylene: Effect of solid‐state shear pulverization on crosslinks, branches, and chain lengths

Abstract: Crosslinked low-density polyethylene (XLLDPE) is widely used in several specialty plastics industries. However, the permanent chemical crosslinks cause high-melt viscosity and poor processability, preventing the material from being reused and recycled effectively. This study investigates solid-state shear pulverization (SSSP) as a continuous, commercially viable mechanochemical processing technique to initiate the decrosslinking of XLLDPE for mechanical recycling. Post-industrial XLLDPE scrap material was proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In the present investigation, the recycled HDPE (rHDPE/CaCO 3 , designated as ENB‐00 in Table 1) obtained from post‐consumer plastic bags showed an average tensile of 12.4 MPa, modulus of 967 MPa, and strain‐at‐failure of 6% strength after melt reprocessing and compression molding. This value of tensile strength of rHDPE is low compared to virgin HDPE but similar to that of low‐density polyethylene 9,28–30 . The relatively low tensile properties of the rHDPE resin sourced from post‐consumer streams are likely due to various factors, including an inferior‐grade recycled HDPE resin reprocessed multiple times.…”
Section: Resultsmentioning
confidence: 90%
“…In the present investigation, the recycled HDPE (rHDPE/CaCO 3 , designated as ENB‐00 in Table 1) obtained from post‐consumer plastic bags showed an average tensile of 12.4 MPa, modulus of 967 MPa, and strain‐at‐failure of 6% strength after melt reprocessing and compression molding. This value of tensile strength of rHDPE is low compared to virgin HDPE but similar to that of low‐density polyethylene 9,28–30 . The relatively low tensile properties of the rHDPE resin sourced from post‐consumer streams are likely due to various factors, including an inferior‐grade recycled HDPE resin reprocessed multiple times.…”
Section: Resultsmentioning
confidence: 90%
“…[ 4,5 ] However, the permanent covalent bonds lead to inferior processability which makes recycling and reusing of XLPE more difficult compared to PE. [ 3,6,7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 31–34 ] Both virgin and recycled homopolymers were effectively processed with SSSP to modify the macromolecular chains in ways that enhance crystallinity and crystallization rate, mechanical properties, and melt‐processability. [ 35–38,41 ]…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state shear pulverization (SSSP) is an alternative technique to the industry standard twin screw extrusion (TSE), [25,26] processing polymers through shear and compressive mechanochemistry at temperatures below their melting and vitrification temperatures. [12,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] SSSP is a continuous and industrially scalable process that does not use monomers, solvents, or processing aids and therefore is logistically simple and environmentally benign. Previous reports have shown that SSSP can prepare materials with improved properties through favorable nano-and micron-scale morphology development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation